2020
DOI: 10.31167/csecfv0i45.19887
|View full text |Cite
|
Sign up to set email alerts
|

Estimación del área basimétrica en masas maduras de Pinus sylvestris en base a una única medición del escáner láser terrestre (TLS)

Abstract: El láser escáner terrestre (TLS) ha surgido como un nuevo dispositivo de tecnología LiDAR con un gran potencial para ser implementado en inventarios forestales (IIFF). En este trabajo se ha desarrollado un algoritmo con el que se obtienen métricas capaces de estimar el área basimétrica a nivel de parcela (G) en base a una única medición del TLS. El estudio se ha realizado en masas maduras de Pinus sylvestris, inventariadas mediante una red de 40 parcelas que cubren casi por completo el área de distribución y r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Regarding the error obtained in each parameter, the combination of scans 0-5-6-7-8 for AGB obtained an error of 1.61 t•ha −1 , which was below the one presented by other authors [10] who used the same methodology, but in tropical environments. For BA (scan combination 0-5-6-7-8) the error obtained was 5.35 m 2 •ha −1 , improving those obtained by Molina-Valero et al [47], with an RMSE of 8.57 m 2 •ha −1 for pure plots of P. sylvestris L. with a radius of 7 m and performing a single TLS measurement from the plot center. The error obtained in the estimation of the CBH with the combination of three scans (5-0-7) was 0.83 m lower than 1.95 m obtained by Giannetti et al [48] in the CBH study performed on a set of individual trees of Cupressus sempervirens L. and P. pinaster with eight scanner positions.…”
Section: Discussionsupporting
confidence: 57%
“…Regarding the error obtained in each parameter, the combination of scans 0-5-6-7-8 for AGB obtained an error of 1.61 t•ha −1 , which was below the one presented by other authors [10] who used the same methodology, but in tropical environments. For BA (scan combination 0-5-6-7-8) the error obtained was 5.35 m 2 •ha −1 , improving those obtained by Molina-Valero et al [47], with an RMSE of 8.57 m 2 •ha −1 for pure plots of P. sylvestris L. with a radius of 7 m and performing a single TLS measurement from the plot center. The error obtained in the estimation of the CBH with the combination of three scans (5-0-7) was 0.83 m lower than 1.95 m obtained by Giannetti et al [48] in the CBH study performed on a set of individual trees of Cupressus sempervirens L. and P. pinaster with eight scanner positions.…”
Section: Discussionsupporting
confidence: 57%
“…Strahler et al [91] obtained an error of 15.49% in the estimation of basal area in a P. ponderosa stand in New South Wales (Australia) with a single scan; in a study with 30 scan plots installed in six New England hardwood and conifer forest stands, Yao et al [92] explained 66% of the observed variability in G, with an RMSE% value of 15.24% and 85% of the variability observed in W, with an RMSE% of 10.69%; Skowronski et al [51] reported RMSE% values for CBD and CFL estimates of 18.48% and 15.68%, respectively, in wildfire-prone stands in the New Jersey Pinelands; Torralba et al [82] explained 70% of the observed variability in W with an RMSE% of 21% in Mediterranean forests using TLS-metrics obtained with a single scan similar to those used in this study; in a study of 40 plots in mature P. sylvestris forests in Spain, Molina-Valero et al [93] estimated G from a single scan with an RMSE% of 21.84%, and explained 75% of the observed variability.…”
Section: Models Based On Tls-derived Metricsmentioning
confidence: 65%
“…This is done by the normalize function ( Figure 1), which obtains coordinates relative to the plot centre and the digital terrain model. This function also applies the point cropping process as a criterion for reducing point density homogeneously in space and proportional to object size [10].…”
Section: Detection Of Trees and Estimation Of Dbhmentioning
confidence: 99%